Good Practices Implemented by the Centro de Capacitación en Educación a Distancia (CECED, Distance Education Training Center) in Accordance with ISO 21001:2018 Educational Organizations — Management Systems for Educational Organizations — Requirements wit (Revista Electrónica Calidad en la Educación Superior, 2025)
The competence of staff in educational organizations, along with their ongoing professional development, is a key requirement for enhancing the satisfaction of students and other stakeholders. At the State Distance University (UNED), the Center for Training in Distance Education (CECED) is responsible for providing academic staff with training in didactics and distance education methodologies. This essay aims to evaluate the implementation of good practices at CECED derived from the ISO 21001:2018 standard Educational Organizations — Management Systems for Educational Organizations — Requirements with guidance for use, based on an analysis of current regulations and the information provided by the Center’s coordinator. The discussion is organized into three sections: the mission of CECED, the ISO 21001:2018 standard, and the good practices of CECED in alignment with standard. The conclusion is that CECED successfully adheres to the good practices outlined in the ISO 21001:2018 standard.
Keywords: workforce training; professional development; teacher training; ISO 21001:2018; educational organizations; CECED; distance education